Case Report: A case report and literature review of hemoglobin variation associated with neonatal cyanosis - Chen, Yanru; Lv, Jingwen; Qian, Jihong (Frontiers in Pediatrics, 2024)
We will discuss a recent case of unexplained neonatal cyanosis, evaluate its origin, clinical presentation, diagnosis, and treatment, and share with you some of our clinical insights. We report a transient cyanosis in a newborn due to a mutation in the globulin gene (HBG2), as well as diagnosis and treatment. Clinically, the infant was in good overall health, and despite low oxygen saturation, the arterial oxygen partial pressure was always normal. Early respiratory support includes mechanical ventilation, nasal tube oxygen, and eventually stopping oxygen therapy. With the above treatment measures, the blood oxygen saturation of the child always fluctuated at 85%, but the arterial blood oxygen partial pressure was up to 306 mmHg. Further improvement of laboratory tests revealed elevated methemoglobin levels, reticulocytosis, mild anemia, and basically normal on chest X ray and echocardiography. To clarify the etiology, WES testing was performed. The results showed heterozygous variation in HBG2 gene (c.190C> T. p.H64Y). There is heterozygous variation at this site in the proband father, and no variation at this site in the proband mother. Given the age of the affected infants, we hypothesized that the mutation originated in the gamma peptide chain of the head protein. The baby was discharged from the hospital 10 days after birth, with blood oxygen saturation fluctuating around 90%. The cyanosis disappeared 2 months after discharge, and the blood oxygen saturation level returned to normal.We intend to share some clinical experience in the diagnosis and treatment of unexplained neonatal cyanosis by summarizing a newly identified case of the disease and assessing its genesis,